Soil attributes functionality and water eutrophication in the surrounding area of Itaparica Reservoir, Brazil - José C. de Araújo Filho; Günter Gunkel; Maria C. M. Sobral; Martin Kaupenjohann; Helio L. Lopes (Revista Brasileira de Engenharia Agrícola e Ambiental)
In semi-arid areas of Brazil, climate and geological conditions are important factors that restrict the availability of soils and water for sustainable irrigated agriculture. The main objective of this study was to evaluate functionalities of physical and chemical attributes of soils and to provide information about irrigation water quality in the margins of the Itaparica Reservoir aiming the sustainable land use. Available data of 44 representative soil profiles comprising 21 profiles of Arenosols, six of Ferralsols, five of Luvisols, six of Planosols and six of Cambisols were used. Water samples along the margins of the reservoir were analysed to obtain information on water quality. The results indicated a narrow relationship between the functionalities of physical and chemical attributes and the parent material of the soils. The low nutrient availability and high water permeability are the typical characteristics of the soils developed on the sandy covers. On the other hand, higher nutrient availability and permeability restrictions are the most important features of the soils with larger influence of fine sediments. The results also suggested the process of water eutrophication in the Itaparica Reservoir.